Applying an ensemble-based model to travel choice behavior in travel demand forecasting under uncertainties. Issue 6 (2nd July 2020) - Cheng, Long; Lai, Xinjun; Chen, Xuewu; Yang, Shuo; De Vos, Jonas; Witlox, Frank
ABSTRACT: The application of travel demand models to transportation planning has triggered great interests in issues that potentially improve the accuracy of model forecasts. These forecasts, however, are subject to various sources of input and model uncertainties. Focusing on travel choice behavior, this paper draws attention to the use of an ensemble-based model for addressing these uncertainties. A random multinomial logit (RMNL) model is developed by assembling a collection of multinomial logit (MNL) models. The bootstrapping procedure and the random feature selection are employed to capture the uncertainties in the model. A case study of investigating travel mode choice behaviors that illustrates situations necessitating the RMNL model is presented. Results suggest that the uncertainty related to predictions is reduced and the prediction accuracy is much improved. The RMNL model is computationally efficient and provides useful interpretations by estimating variable significance. Also, the RMNL model is able to deal with high-dimensional data.